THE INFLUENCE OF TAXATION KNOWLEDGE AND INCOME TAX REPORTING IN ARTICLE 21 KNOWLEDGE ON COMPLIANCE AND THE USE OF E- FILING REQUIRED TAX OFFICER OF STIE PERBANAS SURABAYA - Anggraini Puspitasari, Dian; Supriyati, . (Buletin Studi Ekonomi; VOL.20.NO.1.FEBRUARI 2015 (PP 1-82), 2016)
The Influence Of Taxation Knowledge And Income Tax Reporting In Article 21 Knowledge On Compliance And The Use Of E- Filing Required Tax Officer Of Stie Perbanas Surabaya. This study aims to test the impact of taxation and income tax reporting in article 21 knowledge on compliance and the use of e-filing by tax payer as the officer of STIE Perbanas Surabaya. A quantitative analysis method (multiple linear regressions) was used to test the data (collected by using a questionnaire). The respondents are the officers of STIE Perbanas Surabaya (as tax payers) who use e-filing. By this research found that tax knowledge has no effect on the use of e-filing, while the income tax reporting in article 21 knowledge has an influence on the use of e-filing.   Keywords: taxation knowledge, income tax reporting in article 21 knowledge, tax payer compliance, the use of e-filing
Keywords: taxation knowledge, income tax reporting in article 21 knowledge, tax payer compliance, the use of e-filing